C−N Cross‐Coupling Reactions Under Mild Conditions Using Singlet Di‐Radical Nickel(II)‐Complexes as Catalyst: N‐Arylation and Quinazoline Synthesis. Issue 18 (13th August 2019) - Sikari, Rina; Sinha, Suman; Chakraborty, Gargi; Das, Siuli; van Leest, Nicolaas Petrus; Paul, Nanda D.
Abstract: Herein we report a cost‐effective synthetic approach for C−N cross‐coupling reactions of a broad array of nitrogen nucleophiles and aryl halides under mild conditions. These reactions are catalyzed by an inexpensive, air‐stable, earth‐abundant and easy‐to‐prepare singlet di‐radical nickel(II)‐catalyst containing two antiferromagnetically coupled single‐electron oxidized diiminosemiquinonato type ligands. This protocol provides an alternative method for C−N cross‐coupling reactions avoiding nickel(0)/nickel(II) or nickel(I)/nickel(III) redox processes via cooperative participation of metal and ligand‐centered redox events. Besides a wide range of N‐arylation reactions, by judicious choice of aryl halides and nitrogen nucleophiles the synthesis of a variety of polysubstituted quinazolines has been achieved in moderate to good yields under relatively mild reaction conditions. Our catalyst has been found to be almost equally effective in quinazoline synthesis via C−N cross‐coupling of (i) 2‐bromobenzylamine with benzamide, and (ii) 2‐bromobenzylbromide with amidine. Control experiments and DFT studies were performed to improve the understanding of the cooperative participation of ligand and metal (nickel)‐centered redox events during oxidative addition/reductive elimination processes of the catalytic cycle and to shed light on the plausible mechanistic pathway of the C−N cross‐coupling reactions. Abstract :